Sustainability and Organizational Change - Catălina Sitnikov (Amfiteatru Economic)
The relevant and, above all, remarkable feature of sustainability is due to its "duality": on the one hand, it is an indispensable element within the companies even if, on the other hand, it increases the costs of many activities and processes. Facing the challenge of sustainability will determine and create, in the coming years, emerging organizational forms. If ten years ago, many managers clearly expressed their doubts regarding the financial feasibility of sustainability, today, they admit the importance of sustainability for the competitive advantage of the companies they manage. Currently, companies have great opportunities to support build a sustainable global economy, becoming one of the solutions to the most pressing societal challenges. Whether it is about reducing pollution, global warming, reducing use of water resources and other limited resources or ensuring a better work environment for employees throughout the supply chain, there are many things that companies can and should do.